Implementation of Porter’s Diamond Model in the strategic architecture for agricultural financing development of baitul-maal wat-tamwil - Adistiar Prayoga (Journal of halal product and research (JPHR), 2019)
In 2018, there were 38.7 million workers in agriculture. The high number in the agricultural sector is not accompanied by an increase in the contribution of the total agricultural sector to the value of the Gross Domestic Product. The condition is exacerbated by the lack of accessibility of rural farmers towards farming capital. Although micro, small and medium enterprises (SME’s) loans grew by 8.0 percent (yoy) in 2016, many studies have revealed the dependence of micro farmers (gurem) on access to capital from informal sources which ultimately makes it difficult for them in terms of repaying capital loans because they are trapped in the practice of money lenders. The existence of Islamic Financial Services Cooperatives (Koperasi Jasa Keuangan Syariah-KJKS) is an interesting subject. KJKS, better known as Baitul Maal wat Tamwil (BMT), is hope for increasing the accessibility of the poor to capital sources because BMT plays a cultural role as a funding intermediary and cultural as a social lending institution (qardhul hasan). This study aims to analyze the development of institutional financing based on Baitul Maal Wat Tamwil (BMT) using the Berlian Porter Model approach so that a strategic architecture of agricultural financing development can be formulated based on the competing factors of BMT competitiveness in rural areas. Primary research data was taken in November 2016-January 2017 using the focus group discussion method with expert speakers. The research data is then supplemented by relevant secondary sources in November 2019. The formulation of competitiveness in the Diamond Model is often known to analyze the competitiveness of countries, but several studies reveal that the Berlian Porter approach can be applied to the scale of the country, region, industry, and individual companies, both goods, and services. The ability of an institution to maintain its existence depends on its competitiveness, and in the aggregate will affect the competitiveness of a country.